Effect of nitrogen and potassium fertilization on the production and quality of oil in jatropha curcas l. under the dry and warm climate conditions of colombia (2014)
This study was conducted to assess fruit and seed yield, oil content and oil composition of Jatropha curcas fertilized with different doses of nitrogen and potassium in Espinal (Tolima, Colombia). The yields ranged from 4,570 to 8,800 kg ha-1 of fruits and from 2,430 to 4,746 kg ha-1 of seeds. These yields showed that the fertilizer dose of 150 kg ha-1 N + 120 kg ha-1 K increased fruit production by 92% and seed production by 95%, which represents an increase of about 100% in oil production, which increased from 947 to 1,900 kg ha-1. The total oil content in the seeds ranged from 38.7 to 40.1% (w/w), with a high content of the unsaturated fatty acids oleic ( and gt; 47%) and linoleic acid ( and gt; 29%). The highest content of oleic acid in the seed oil was from the unfertilized control plants and plants with an application of 100 kg ha-1 of N and 60 kg ha-1 of K, with an average of 48%. The lowest content of oleic acid was registered when a low dose of nitrogen and a high level of potassium were applied at a ratio of 1:2.4 and doses of 50 kg ha-1 N + 120 kg ha-1 K, respectively. Low contents of the saturated fatty acids palmitic (13.4%) and stearic (7.26%) were obtained, making this oil suitable for biodiesel production. The nitrogen was a more important nutrient for the production and quality of oil in J. curcas than potassium under the studied conditions of soil and climate.